Ultra-fast laser pulses induced phase changes in ηǦMo4O11 crystals - Borovšak, Miloš; Mihailović, Dragan (Anali PAZU, 2022)
The article presents the experimental result of fluence dependence of the transient reflectivity response to ultra-fast laser pulses in η-Mo4O11 crystals. Results of the experiment show that at certain fluences at low temperatures phase changes can be induced in the crystals which are not seen inthe temperature phase diagram.